Experiences of Student Participation in Secondary Schools from Representative Organizations (Lima, Peru) - Linares-Campos, Carmen del Rosario (2025)
Objective. This research article aims to identify the characteristics of students’ participation experiences in relation to how representative organizations function with the purpose of recognizing elements that achieve quality participation (understood as autonomy vis-à-vis adults) and critical-thinking capacity (reflection in the face of a social problem). Methodology. A multiple-case study design was implemented in three schools that promote student participation. The sample consisted of final-year secondary students, who, through a sequential process, completed a questionnaire and participated in three focus groups and six individual interviews within the case-study framework. The analysis was descriptive and comprehensive. The descriptive type was used in the questionnaires through statistical analysis. The comprehensive one was applied to qualitative techniques using inductive and deductive coding. Results. There are differences in the quality and critical-thinking capacity of the experience depending on how the student organizations function. Regarding quality, age-related factors must be considered when examining these experiences. Concerning critical-thinking capacity, the institutional and social reach is essential for achieving higher levels of social thinking. Conclusions. Experiences can form citizenship, since they involve reduced adult intervention and the deliberation of social issues. However, the quality and critical-thinking capacity of these experiences in the Peruvian educational field need to be improved. Implications. The study gives an account, from the student perspective, of the characteristics of the experiences and makes it possible to understand those elements that may enhance them.